Laser driven structured quantum rings. (17th April 2015) - Castiglia, Giuseppe; Corso, Pietro Paolo; Giovannini, Umberto De; Fiordilino, Emilio; Frusteri, Biagio
Abstract: In this work we study harmonic emission from structured quantum rings (SQRs). In SQRs, electrons trapped in two-dimensional structures are further confined by an external potential composed of N scattering centers arranged on a circle. We build a suitable one-dimensional model Hamiltonian describing this class of systems and analytically solve the associated Schödinger equation. We find that the solution can be expressed in terms of Mathieu functions and focus on the specific case of N = 6. By exactly solving the time-dependent Schödinger equation, we then show how the harmonic response to linearly polarized lasers strongly depends on the ring physical parameters. The results illustrate how the additional degrees of freedom introduced by these parameters provide important handles to control the emitted spectrum that in some cases extends into the XUV region.